GABOR FILTER FOR FINGERPRINT RECOGNITION: A REVIEW - P. P. Dadhich, S. Borse (International Journal of Research Science and Management, 2015)
Many researchers continue to experiment with Gabor filter in area of biometrics identification which also includes fingerprint recognition. Gabor filters have been widely used for feature extraction in fingerprint identification. This paper attempts to present a survey of fingerprint recognition methods that employ various Gabor filter based approaches in feature extraction.